Unmake up your mind: why some reversible decisions lead to more choice satisfaction than others. - Moisieiev, Dmytro (Cranfield University, 2018)
Consumers can often make reversible decisions, e.g. make purchases where items can be returned for exchanges or refunds or where purchases can be cancelled. Having the option to reverse a purchase decision (decision reversibility) has been linked to lower choice satisfaction, prompting scholars to think that being able to return goods for a refund or to cancel a purchase should make consumers less satisfied with their purchases. In this thesis I qualify this notion. I refine the construct of reversible decisions, showing that there are two distinct kinds of them: when consumers have an option to remake a choice (exchange the chosen item for a non-chosen one) and when consumers have an option to unmake a choice (cancel an order or return items for a refund). I conduct four experiments that show that consumers who can unmake a choice are more satisfied with it than those who can remake it. I thus refine the link between reversible decisions and choice satisfaction and recommend that retailers do not adopt exchange-only return policies. I explain the mediating mechanism for this effect: the extent of post-choice comparison between the chosen and foregone alternatives that is higher in decisions where a choice can be remade, rather than unmade. I also show that the effect of the different decision reversibility options (unmake choice vs remake choice) on choice satisfaction is stronger for neurotic consumers. Cognitively depleting consumers or prompting them to seek variety in their choices removes the effect of decision reversibility options on choice satisfaction, suggesting some ways in which retailers can contain consumers’ dissatisfaction with exchange-only return policies.
Keywords: Decision reversibility; decision satisfaction; return policies; cancellations; comparative thinking; post-choice comparison